GURU DALAM PENDIDIKAN KARAKTER - Sekarini, Ni Made (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
In terms of providing reinforcement for character education, a strong foundation must be found to build aspects of character-strengthening. That’s why character education is crucial to develop at school. The aim is to form a nation that is strong, competitive, has a noble character, moral, tolerant, works together, has a patriotic spirit, develops dynamically, has science and technology-oriented, imbued with faith and devotion to God Almighty based on Pancasila. A tough national character is a reflection of a strong nation. Its implementation involves all educational centers, from the family environment, school environment and community environment. Globalization, progress in the world of education and advances in digital technology make the challenges of character education increasingly complex. Therefore, formal education at school should be outlined in the curriculum, carried out in all fields of study and implemented through appropriate learning methods that can provide space for character development every day so that it becomes a habit and becomes a culture. On the other hand, can not be avoided the important roles of the teachers in these circumstances. How the teachers take part in it, can be the point of the successful of the character education.